The isolation and characterisation of antibacterial compounds from Combretum erythrophyllum (Burch.) Sond. - Eloff, Jacobus Nicolaas (University of Pretoria, 2013)
Dissertation (PhD(Pharmacology))--University of Pretoria, 2003.